A Computer Assisted Language Learning Development via Top Level Structure to Enhance Reading Comprehension for Nakhon Ratchasima Rajabhat University’s Undergraduate Students: Phase 2 - เติมสินสุข, สายสุนีย์ (Ratchaphruek Journal, 2019)
Computer assisted language learning (CALL) development via top level structure (TLS) is a teaching innovation for English. It was developed to enhance reading comprehension of undergraduate students using a research and development methodology. The study was conducted in the academic year 2017-2018, and it was a continuation based on phase 1 research results. The purposes of this phase 2 study, were to 1) develop the efficiency of CALL-TLS to the designated criterion, 2) investigate the students’ reading comprehension progress after learning via CALL-TLS, and 3) compare the students’ reading comprehension before and after learning via CALL-TLS. The sample group was 30 Nakhon Ratchasima Rajabhat University (NRRU) undergraduates who had registered in an English for Communication II course in academic year 2018; the sample group was randomized using stratified random sampling. Research instruments used in this study were: a reading comprehension test, and a CALL-TLS evaluation form. The data were then analyzed by percentage, mean, and t-test dependent sample. The results of the study were: 1) that CALL-TLS met the designated criterion of efficiency development to enhance the students’ reading comprehension, 2) after learning via CALL-TLS, the students made higher reading comprehension progress than the designated criterion, and 3) after learning via CALL-TLS, the students performed with higher reading comprehension than before learning via CALL-TLS at .05 level of significance.